APLIKASI 6 SIGMA DALAM MENURUNKAN MALFUNCTION DEFECT DI PENGETESAN ELEKTRIKAL (AC TRANSIENT TEST) PADA TAHAPAN PENGEMBANGAN PRODUK BLU-RAY DISC PLAYER (STUDI KASUS DI PERUSAHAAN MANUFAKTUR ELEKTRONIK) - Dony Arief Widiatmoko; Waseso Segoro (Universitas Mercu Buana, 2015)
Abstract. The research helds inelectrical product manufacturing company, focus of theproduct is Blu-ray Disc Player. The dominant problem caused by electrical test at the productdevelopment process is Malfunction at AC Transient test where contribution is 83% fromtotal electrical problem. Main objectives of this research are to determine the vital factors andprovide optimal solution to reduce/elimate these problem at development stage. The problemsolving methodology using Six Sigma DMAIC and DOE .The analysis indicated that linefilter value and spark gap distance in the PCB SMPS are vital factors that influence themalfunction defective as AC Transient test result. The design of experiment (DOE) techniqueuse to define the optimum values of vital factor‟s needed to reduce/eliminate the defect. As aresult, a reduction of malfunction defective at AC Transient test was achieved, from 125000ppm to 0 ppm and thus improve its Sigma level from 2.65 to 6.Keywords:Defective reduction, DMAIC, DOE, malfunction defective, AC Transient test.